French Students of Maghreb Background and Entrepreneurship - Meghouar, Hicham (International Journal of Business, Economics and Management, 2014)
The aim of this article is to analyze the theoretical motivations for entrepreneurship among French students of Maghreb background (hereafter FSMB). Indeed, there are two opposing logics: the entrepreneurial logic, and the social integration one. Is entrepreneurship still seen as a last chance for these young studentswho are stigmatized (Goffman, 1975) and socially labeled (Becker, 1985), and who remain very often unemployed after graduation? Or does it fit in the context of the ambitious individual who wants to find a place of one’s own in an increasingly competitive social environment. This study also addresses the question of ethnic entrepreneurship by analyzing the specificity of the potential corporate projects of the French students of North African origins.